Hungarian Monitoring, 24 May 1988 . [Magyar rádiófigyelő], 1988. május 24 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Soviet supreme council term - Situation in Nicaragua - Famine in North Vietnam Domestic Affairs: - Grósz's interview in Magyar Hírlap - Magyar Nemzet lead article: socialist society being built from below - Ministerial review at the Gabčíkovo-Nagymaros dam - Veszprém conference on ethics Economy: - Cooperatives, tax reform, companies law, buying shares Külpolitika - A szovjet legfelsőbb tanács időszaka - Nicaraguai helyzet - Éhínség Észak - Vietnamban Belpolitika: - Grósz interjú a Magyar Hírlapban - Magyar Nemzet vezércikk: az alulról építkező szocialista társadalom - Miniszteri szemle a bős-nagymarosi vízlépcsőnél - Veszprémi etikai konferencia Gazdaság: - Szövetkezetek, adóreform, társasági törvény, részvényvásárlás